Evaluating sustained quality improvements: long‐term effectiveness of a physician‐focused intervention to reduce potentially inappropriate medication prescribing in an older population. (10th March 2014) - Lopatto, J.; Keith, S. W.; Del Canale, S.; Templin, M.; Maio, V.
Summary What is known and objectives Although quality improvement initiatives targeting physician practice patterns have been effective, evidence is lacking on their long‐term sustainability. We previously demonstrated the success of a population‐wide, physician‐focused quality improvement intervention targeting potentially inappropriate prescribing (PIP) in an aged population of the Local Health Authority (LHA) of Parma, Italy. We sought to assess whether the decrease in PIP incidence rates achieved during the intervention was sustained after discontinuation of the intervention, and which factors modified the effectiveness of the intervention. Methods Using a regional administrative claims database, we assessed changes in quarterly PIP exposure incidence rates for each phase [pre‐intervention (2005 Q1‐2007 Q3), intervention (2007 Q4‐2009 Q4) and post‐intervention (2010 Q1‐Q4)] of the study for both all and newly PIP‐exposed patients. Piecewise‐linear longitudinal logistic regression was used to model the odds of PIP exposure. Results 299 GPs (98·7%) serving 111 282 older patients were included. PIP incidence rates declined from 7·1% (pre‐intervention) to 4·9% (intervention), and to 4·3% (post‐intervention). There was no significant change in odds of PIP exposure following the intervention period (P = 0·52), and the rates of change in PIP exposure odds during pre‐intervention and post‐intervention periods were not significantly different (P = 0·39). The intervention was attributed to an 18% long‐term reduction in the odds of PIP exposure. No assessed patient or GP characteristics modified this effect. Results among patients newly exposed to PIP were similar to results among all patients exposed to PIP. What is new and conclusion The significant reduction in the odds of PIP exposure achieved during the intervention was sustained after its discontinuation. Because the intervention showed success across the spectrum of patients and providers, it shows promise for generalizability to other healthcare settings.